A Metamaterial Backed Dipole Antenna for High Gain Directional Communications - Sarin, V. P.; Jayakrishnan, M. P.; Aanandan, C. K.; Pezholil, M.; Kesavath, V. (Advanced Electromagnetics, 2016)
The enhanced radiation performance of a dipole antenna backed by the split ring resonator-continuous wire pair array working in the H┴ excitation scenario is presented in this paper. The H┴ excitation scenario of the metamaterial is used to get zero reflection phase resulting in enhanced gain performance. The two layer meta-structure along with the dipole is fabricated on a low cost substrate of dielectric constant 4.4 and height 1mm. The reflection properties of the metamaterial structure and its effect on the radiation performance of the dipole antenna are presented in this paper.